From animal hibernation to human’s hypometabolism: cellular mechanisms of natural and artificial hypobiosis - Repina, S. V.; Nardid, O. A.; Shylo, O. V.; Kovalenko, I. F. (Ukrainian Antarctic Journal, 2017)
Objective: to carry out a comparative study of structural and functional responses of rats and hamsters RBCs when the animals entered and left an artificial hypobiosis state under conditions of hypothermia-hypoxia-hypercapnia. Methods: RBCs of rats and hamsters: control, in artificial hypobiotic state, 2 and 24 h post-hypobiosis state, and those from winter-hibernating hamsters were investigated. Osmotic resistance was determined by the method of small-angle light scattering. Relative content of main hemoglobin forms (oxy-, deoxy- and metHb) was determined by the method of differential spectrophotometry. Microviscosity of cytosol was evaluated within a range of 37-0°C by EPR spin probe method. Results: the artificial hypobiotic state was characterized by body temperature decreasing (down to 16°C), in the same way for both homoiothermal and heterothermal mammals. This was accompanied by changes of osmotic resistance, redistribution of main hemoglobin forms, cytosol microviscosity in RBCs. Increased osmotic resistance and significantly elevated relative content of oxyHb were revealed in 2 h after hypobiotic state. Modifications of the parameters kept changing up to 24 h post-hypobiotic-state. RBC responses to natural and artificial hypobiosis had common as well as different features. Difference in the reaction of RBC cytosol of homoiotherms and heterotherms, associated with the season, was found. Conclusions: RBCs response in vivo to physiological rearrangements induced by artificial hypobiosis of both heterotherm and homoiotherm mammals. The significant changes of the structural and functional state of erythrocyte kept changing up to 24 h post-hypobiotic-state, while the physiological state of the animals was similar to the control already in 2 hours after hypobiosis. Existence of mammals RBC “aftersensations” in posthypobiotic state allows to consider the model of artificial hypobiosis perspective for clarification of the cellular mechanisms of controlled induction of hypometabolic state.